Electrochemical device and electronic device
Patent Information
- Application Number
- CN202280100103.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-29
- Publication Date
- 2025-04-22
AI Technical Summary
Existing cathode active materials for electrochemical devices have poor cycle performance at high temperatures and insufficient safety performance, mainly due to their poor structural stability and thermal stability.
Doping elements such as aluminum (Al), magnesium (Mg), zirconium (Zr) and titanium (Ti) are used to improve the cathode active material, and polynitrile additives and cyclic sulfonate additives are added to the electrolyte. An interface protective film (CEI film) is formed to improve the structure and thermal stability of the cathode active material.
It significantly improves the cycle performance and safety performance of the electrochemical device, reduces the risk of transition metal dissolution and side reactions on the surface of the positive active material, reduces heat generation, and enhances the stability and safety of the electrochemical device at high temperatures.
Abstract
Description
Electrochemical devices and electronic devices Technical Field
[0001] The present application relates to the field of energy storage technology, and more specifically, to electrochemical devices and electronic devices. Background Art
[0002] Electrochemical devices, with their high energy density, high operating voltage, and lightweight characteristics, are widely used in electronic products such as mobile phones, laptops, and cameras. While improving the electrochemical performance of electrochemical devices, their safety performance cannot be ignored. As the performance requirements of electronic products increase, the performance requirements for electrochemical devices are also gradually increasing.
[0003] Research has found that the insertion and extraction of metal ions contained in the positive electrode active material within an electrochemical device is a core process of charge and discharge, and thus the positive electrode active material has a significant impact on the performance of the electrochemical device. However, existing positive electrode active materials have poor structural stability and inherent thermal stability, which leads to poor cycling performance of electrochemical devices at high temperatures. Therefore, it is imperative to develop a positive electrode active material with excellent thermal stability that can improve the cycling performance of electrochemical devices.
[0004] Summary of the Invention
[0005] The present application provides an electrochemical device and an electronic device. The positive electrode active material contained in the electrochemical device has good thermal stability, and the electrochemical device has good cycle performance.
[0006] In the first aspect, the present application proposes an electrochemical device. The electrochemical device includes a negative electrode, a positive electrode, a separator and an electrolyte. The positive electrode includes a positive electrode active material containing a doping element, the doping element including one or more of aluminum Al, magnesium Mg, zirconium Zr, titanium Ti and lanthanum La, and the mass percentage of the doping element based on the mass of the positive electrode active material is b%, 0.01≤b≤3; the separator is arranged between the negative electrode and the positive electrode; the electrolyte includes a polynitrile additive, the polynitrile additive includes a compound represented by formula (IA) and / or a compound represented by formula (II-A),
[0007]
[0008] In Formula IA, A 11 、A 12 、A 13 Each independently selected from formula (I-A1), formula (I-A2),
[0009]
[0010] In Formula IA, n is a positive integer from 1 to 8, wherein when there are multiple A 11When multiple A 11 Can be the same or different, A 11 、A 12 、A 13 At least two of which are selected from I-A2;
[0011] In formula II-A, Q is selected from one of formula (II-A1) and formula (II-A2);
[0012]
[0013] In formula II-A, m is selected from 1 or 2;
[0014] R 11 、R 12 、R 13 、R 21 、R 22 、R 23 are independently selected from a covalent single bond, a substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkynyl, substituted or unsubstituted C6-C 10 aryl, substituted or unsubstituted C3-C 10 alicyclic hydrocarbon group, substituted or unsubstituted C1-C 10 The heterocyclic group, substituted or unsubstituted heteroatom-containing functional group, when R 11 、R 12 、R 13 、R 21 、R 22 、R 23 When at least one of is substituted, the substituent is selected from halogen;
[0015] The heterocyclic group includes at least one of an aliphatic heterocyclic group and an aromatic heterocyclic group;
[0016] in, Indicates the binding site with the adjacent atoms.
[0017] In some embodiments, based on the mass of the electrolyte, the mass percentage of the polynitrile additive is X;
[0018] 0.15≤X / b≤100; optionally, 1≤X / b≤50.
[0019] In some embodiments, the number of formula (I-A2) in the compound represented by formula (IA) is 4 to 10.
[0020] In some embodiments, the polynitrile additive includes at least one of the compounds represented by formula (I-1) to formula (I-17),
[0021]
[0022]
[0023]
[0024] In some embodiments, the polynitrile additive includes at least one of the compounds represented by formula (II-1) to formula (II-21),
[0025]
[0026]
[0027] In some embodiments, the electrolyte further comprises a cyclic sulfonate additive, wherein the cyclic sulfonate additive comprises a compound represented by formula (III):
[0028]
[0029] wherein D and E are each independently selected from a substituted or unsubstituted C1 to C8 alkylene group, and when substituted, the substituent is selected from a fluorine atom;
[0030] Alternatively, D and E are each independently selected from substituted or unsubstituted C1 to C6 alkylene;
[0031] Further optionally, D and E are each independently selected from substituted or unsubstituted C1 to C4 alkylene;
[0032] Selected from a covalent single bond or -OS(=O)2-.
[0033] In some embodiments, the cyclic sulfonate additive includes a compound represented by formula (III-1),
[0034]
[0035] Among them, R 31 and R 32 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group;
[0036] s is a positive integer from 1 to 4.
[0037] In some embodiments, the cyclic sulfonate additive includes a compound represented by formula (III-2),
[0038]
[0039] Among them, R 33 and R 34 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group;
[0040] R 35 and R 36 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group;
[0041] r is a positive integer from 1 to 4. When r≥2, multiple R 35 can be the same or different from each other, and multiple R 36 They may be the same as or different from each other.
[0042] In some embodiments, the cyclic sulfonate additive includes one or more of 1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 1,2-butane sultone, 1,3-butane sultone, 2,4-butane sultone, 1,3-pentane sultone, methylene methanedisulfonate, or ethylene methanedisulfonate.
[0043] In some embodiments, the mass percentage of the cyclic sulfonate additive is c%, based on the weight of the electrolyte, and 0.10≤c≤10; optionally, the ratio of the mass percentage of the doping element b% to the mass percentage of the cyclic sulfonate additive c% satisfies: 0.005≤b / c≤20.
[0044] In some embodiments, the doping element is magnesium (Mg); optionally, 0.01≤b≤0.5.
[0045] In some embodiments, the positive active material includes first particles and second particles, and the average particle size of the first particles is larger than the average particle size of the second particles.
[0046] In some embodiments, the positive electrode active material satisfies at least one of the following conditions:
[0047] The Dv50 of the first particle satisfies: 10 μm ≤ Dv50 ≤ 15 μm;
[0048] The Dv99 of the first particle satisfies: 20 μm ≤ Dv99 ≤ 30 μm;
[0049] The ratio between Dv50 and Dv99 of the first particle satisfies: 1.5≤Dv99 / Dv50<3;
[0050] The Dv50' of the second particle satisfies: 2 μm ≤ Dv50' ≤ 6 μm;
[0051] The Dv50 of the first particle and the Dv50' of the second particle satisfy: 2≤Dv50 / Dv50'<8.
[0052] In some embodiments, the ratio of Dv50 of the first particles to the mass percentage X% of the polynitrile additive satisfies: 7≤Dv50 / X≤50; alternatively, 10≤Dv50 / X≤30.
[0053] In some embodiments, after the electrochemical device is fully charged to 4.5 V, differential scanning calorimetry is used to test the positive electrode, which shows an exothermic peak at 250° C. to 300° C.
[0054] In a second aspect, the present application proposes an electronic device comprising an electrochemical device as in any embodiment of the first aspect of the present application.
[0055] According to the electrochemical device of the embodiment of the present application, the positive electrode active material contains a doping element with a mass percentage of 0.01 to 3, and the doping element can improve the structural stability and thermal stability of the positive electrode active material after delithiation. In addition, the compound represented by formula (IA) and the compound represented by formula (II-A) are added to the electrolyte of the electrochemical device. The above-mentioned compounds can form an interface protection film such as a CEI film on the surface of the positive electrode active material. On the one hand, the CEI film can effectively reduce the dissolution of transition metals on the surface of the positive electrode active material, further improve the structural stability of the positive electrode active material, and thus improve the cycle performance of the electrochemical device; on the other hand, the CEI film can separate the positive electrode active material and the electrolyte, reduce the risk of side reactions on the surface of the positive electrode active material, thereby reducing the heat generated by the side reactions. In other words, it can reduce the heat generated at the interface of the positive electrode active material, thereby further improving the thermal stability of the positive electrode active material, thereby improving the cycle performance of the electrochemical device at high temperature, and can reduce the risk of expansion, spontaneous combustion, etc. due to heat accumulation inside the electrochemical device, thereby improving the safety performance of the electrochemical device. Therefore, the interaction between the doping elements of the positive electrode active material and the polynitrile additive in the electrolyte can significantly improve the structural stability and thermal stability of the positive electrode active material, and can enhance the cycle performance and safety performance of the electrochemical device. DETAILED DESCRIPTION
[0056] The embodiments of the present application will be described in detail below. Throughout this specification, identical or similar components and components having identical or similar functions are represented by similar reference numerals. The embodiments described herein with respect to the accompanying drawings are illustrative and diagrammatic and are intended to provide a basic understanding of the present application. The embodiments of the present application should not be construed as limiting the present application.
[0057] In addition, amounts, ratios, and other numerical values are sometimes presented herein in a range format. It should be understood that such a range format is used for convenience and brevity and should be interpreted flexibly to include not only the values explicitly specified as limits of the range, but also all individual values or sub-ranges encompassed within the range, as if each value and sub-range were explicitly specified.
[0058] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "one or more of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0059] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, an alkyl group may be C1-C 50 Alkyl, C1-C 40 Alkyl, C1-C 30 Alkyl, C1-C 20 Alkyl, C1-C 12 Alkyl, C1-C 10 In some embodiments, the alkyl group includes methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, etc. In addition, the alkyl group can be optionally substituted.
[0060] The term "alkylene" refers to a group formed by losing two hydrogen atoms from the same carbon of an alkane, or losing one hydrogen atom from each of two different carbons. For example, an alkylene group can be C1-C 50 Alkylene, C1-C 40 Alkylene, C1-C 30 Alkylene, C1-C 20 Alkylene, C1-C 12 Alkylene, C1-C 10 Alkylene, C1-C6 alkylene, C1-C4 alkylene. In some embodiments, alkylene includes methylene-CH2-, ethylene, 1,2-ethylene, propylene, 1,2-propylene, butylene, 1,2-butylene, 1,3-butylene, 1,4-butylene, pentylene, 1,2-pentylene, etc. In addition, alkylene can be optionally substituted.
[0061] The term "alkenyl" encompasses both straight and branched chain alkenyl groups. For example, alkenyl groups can be C2-C 50 Alkenyl, C2-C 40 Alkenyl, C2-C 30 Alkenyl, C2-C 20 Alkenyl, C2-C 12 Alkenyl, C2-C 10 In some embodiments, the alkenyl group includes vinyl, propenyl, butenyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, etc. In addition, the alkenyl group can be optionally substituted.
[0062] The term "alkynyl" encompasses both straight and branched chain alkynyl groups. For example, an alkynyl group can be C2-C 50 Alkynyl, C2-C 40 Alkynyl, C2-C 30 Alkynyl, C2-C 20 Alkynyl, C2-C 12 Alkynyl, C2-C 10 Alkynyl, C2-C6 alkynyl, C2-C6 alkynyl, C2-C4 alkynyl. In certain embodiments, alkynyl includes ethynyl, propynyl, butynyl, pentynyl, hexynyl, heptynyl, octynyl and the like. In addition, alkynyl can be optionally substituted.
[0063] The term "aryl" refers to a closed aromatic ring or ring system. For example, an aryl group can be C6-C 50 Aryl, C6-C 40 Aryl, C6-C 30 Aryl, C6-C 20 Aryl, C6-C 10 Aryl. 30 Aryl refers to a group containing 6 to 30 carbon atoms and including an aromatic ring structure. In some embodiments, aryl includes phenyl, naphthyl, phenanthrenyl, anthracenyl, biphenyl, triphenylene, pyrenyl, spirobifluorenyl, phenanthrenyl, peryl, indenyl, and azulenyl.
[0064] The term "aromatic heterocyclic group" refers to an aromatic group in which the carbon atoms in the ring are replaced by heteroatoms, which may include nitrogen atoms, oxygen atoms, sulfur atoms, and the like.
[0065] The term "alicyclic hydrocarbon group" refers to a closed aliphatic ring. For example, an alicyclic group refers to a C3-C 50 Aliphatic ring, C3-C 40 Aliphatic ring, C3-C 30 Aliphatic ring, C3-C 20 Aliphatic ring, C3-C 10 Aliphatic ring, in which C3-C 10Alicyclic refers to a group containing 3 to 10 carbon atoms for forming a ring. In some embodiments, the alicyclic group includes cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cycloheptyl.
[0066] The term "alicyclic group" refers to an alicyclic hydrocarbon group containing heteroatoms, and the heteroatoms may include nitrogen atoms, oxygen atoms, sulfur atoms, and the like.
[0067] The term "heterocyclyl" refers to a ring system containing heteroatoms, such as an aliphatic heterocyclyl or an aromatic heterocyclyl.
[0068] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.
[0069] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0070] In various places of this specification, the substituent of compound is disclosed with group or scope.It is clearly expected that this description comprises each individual subcombination of the member of these groups and scope.For example, it is clearly expected that the term "C1-C8 alkyl" discloses C1, C2, C3, C4, C5, C6, C7, C8, C1-C8, C1-C7, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C8, C2-C7, C2-C6, C2-C5, C2-C4, C2-C3, C3-C8, C3-C7, C3-C6, C3-C5, C3-C4, C4-C8, C4-C7, C4-C6, C4-C5, C5-C8, C5-C7, C5-C6, C6-C8, C6-C7 and C7-C8 alkyl individually.
[0071] As further examples, the integers in the range of 5 to 40 are specifically contemplated as individually disclosing 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, and 40; the integers in the range of 1 to 20 are specifically contemplated as individually disclosing 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. Additional groups or ranges are expressly contemplated accordingly.
[0072] When the above groups are substituted, the substituents may be independently selected from halogen atoms.
[0073] In an electrochemical device under high temperature environment or during charge and discharge cycles, cations in the positive electrode active material contained therein may dissolve, causing the structure of the positive electrode active material to be destroyed, thereby deteriorating its cycle performance at high temperature.
[0074] In view of this, the present application improves the electrochemical device from the perspective of protecting the positive electrode active material, designs the electrolyte and the positive electrode active material at the same time, adds positive electrode protection additives such as polynitrile additives to the electrolyte, so as to form a positive electrode electrolyte interface (Catheode Electrolyte Interphase, CEI) film on the surface of the positive electrode active material, and adjusts the mass percentage of the doping element in the positive electrode active material to reduce the risk of side reactions between the positive electrode active material and the electrolyte. The electrochemical device of the present application is also applicable to electronic devices. The technical solution of the present application is described in detail below.
[0075] In a first aspect, the present application provides an electrochemical device.
[0076] An electrochemical device includes a negative electrode, a positive electrode, a separator, and an electrolyte.
[0077] The positive electrode includes a positive electrode active material containing a doping element. The doping element includes one or more of aluminum Al, magnesium Mg, zirconium Zr, titanium Ti and lanthanum La. Based on the mass of the positive electrode active material, the mass percentage of the doping element is b%, 0.01≤b≤3. Exemplarily, the positive electrode active material may include a transition metal and metallic lithium. The doping element can effectively occupy the transition metal site and / or lithium site in the crystal phase structure, and can improve the structural stability and thermal stability of the positive electrode active material after delithiation during the charging process. In particular, when the positive electrode active material is doped with a doping element (such as one or more of aluminum Al, magnesium Mg, zirconium Zr, titanium Ti and lanthanum La), and the mass percentage b of the doping element meets the above range, the structural stability of the positive electrode active material can be significantly improved, and the thermal stability of the positive electrode active material is also significantly improved.
[0078] The separator is placed between the negative electrode and the positive electrode to separate them and reduce the risk of direct contact between the two electrodes. The negative electrode, separator, and positive electrode can have various structural forms. For example, the negative electrode, separator, and positive electrode are stacked in a laminated structure, or the negative electrode, separator, and positive electrode are wound to form a spiral structure.
[0079] The electrolyte includes a polynitrile additive. During charge and discharge of the electrochemical device, the polynitrile additive can undergo a complexation reaction with the transition metal on the surface of the positive electrode active material, forming a stable CEI film on the surface of the positive electrode active material. The CEI film can protect the positive electrode active material. On the one hand, the CEI film can effectively reduce the dissolution of transition metals on the surface of the positive electrode active material. On the other hand, the CEI film can separate the positive electrode active material and the electrolyte, reducing the risk of side reactions at the positive electrode active material interface, thereby reducing the heat generated by these side reactions. In other words, it can reduce the heat generated at the positive electrode active material interface.
[0080] In some embodiments, the polynitrile additive of the present invention may include a compound represented by formula (IA):
[0081]
[0082] In Formula IA, A 11 、A 12 、A 13 Each independently selected from formula (I-A1), formula (I-A2),
[0083]
[0084] In Formula IA, n is a positive integer from 1 to 8, wherein when there are multiple A 11 When multiple A 11 Can be the same or different, A 11 、A 12 、A 13 At least two of the following are selected from I-A2; wherein n is 1, 2, 3, 4, 5, 6, 7 or 8;
[0085] R 11 、R 12 、R 13 are independently selected from a covalent single bond, a substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkynyl, substituted or unsubstituted C6-C 10 aryl, substituted or unsubstituted C3-C 10 alicyclic hydrocarbon group, substituted or unsubstituted C1-C 10 The heterocyclic group, substituted or unsubstituted heteroatom-containing functional group, R 11 、R 12 、R 13 When at least one of is substituted, the substituent is selected from halogen; further, the substituent may be a fluorine atom.
[0086] The heterocyclic group includes at least one of an aliphatic heterocyclic group and an aromatic heterocyclic group;
[0087] in, Indicates the binding site with the adjacent atoms.
[0088] In other embodiments, the polynitrile additives of the present invention may include a compound represented by formula (II-A),
[0089]
[0090] In Formula II-A, Q is selected from Formula (II-A1) and / or Formula (II-A2);
[0091]
[0092] In formula II-A, m is selected from 1 or 2;
[0093] R 21 、R 22 、R 23 are independently selected from a covalent single bond, a substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkynyl, substituted or unsubstituted C6-C 10 aryl, substituted or unsubstituted C3-C 10 alicyclic hydrocarbon group, substituted or unsubstituted C1-C 10 The heterocyclic group, substituted or unsubstituted heteroatom-containing functional group, when R 21 、R 22 、R 23 When at least one of is substituted, the substituent is selected from halogen; further, the substituent may be a fluorine atom.
[0094] The heterocyclic group includes at least one of an aliphatic heterocyclic group and an aromatic heterocyclic group;
[0095] in, Indicates the binding site with the adjacent atoms.
[0096] In some further embodiments, the polynitrile additive may include a compound represented by formula (IA) and a compound represented by formula (II-A), wherein the compound represented by formula (IA) and the compound represented by formula (II-A) are as described in the above embodiments and will not be repeated here.
[0097] The present application adds the compound shown in formula (IA) and the compound shown in formula (II-A) to the electrolyte to significantly improve the high temperature storage performance and cycle performance of the electrochemical device using it. The possible reason is that the electrolyte contains ether polycyano (-CN) compounds and phosphine polycyano (-CN) compounds, and cyano (-CN) can stabilize the transition metal in the high valence state of the positive electrode and inhibit the continuous decomposition of the electrolyte. In addition, the phosphine polycyano (-CN) compound can form an interface protective film at the positive and negative electrodes to further protect the positive and negative electrode surfaces. Therefore, the electrolyte to which the compound shown in formula IA and the compound shown in formula II-A are added can significantly improve the high temperature storage performance and cycle performance of the electrochemical device using it.
[0098] According to the electrochemical device of the embodiment of the present application, the positive electrode active material contains a doping element with a mass percentage of 0.01% to 3% by mass, and the doping element can improve the structural stability and thermal stability of the positive electrode active material after delithiation. In addition, the compound represented by formula (IA) and the compound represented by formula (II-A) are added to the electrolyte of the electrochemical device. The above-mentioned compounds can form an interface protection film such as a CEI film on the surface of the positive electrode active material. On the one hand, the CEI film can effectively reduce the dissolution of transition metals on the surface of the positive electrode active material, further improve the structural stability of the positive electrode active material, and thus improve the cycle performance of the electrochemical device; on the other hand, the CEI film can separate the positive electrode active material and the electrolyte, reduce the risk of side reactions on the surface of the positive electrode active material, thereby reducing the heat generated by the side reactions. In other words, it can reduce the heat generated at the interface of the positive electrode active material, thereby further improving the thermal stability of the positive electrode active material, thereby improving the cycle performance of the electrochemical device at high temperature, and reducing the risk of expansion, spontaneous combustion, etc. due to heat accumulation inside the electrochemical device, thereby improving the safety performance of the electrochemical device. Therefore, the interaction between the doping elements of the positive electrode active material and the polynitrile additive in the electrolyte can significantly improve the structural stability and thermal stability of the positive electrode active material, and can enhance the cycle performance and safety performance of the electrochemical device.
[0099] [Polynitrile additives for electrolytes]
[0100] The electrolyte of the present application includes a polynitrile additive.
[0101] In some embodiments, the mass percentage of the polynitrile additive is X% based on the mass of the electrolyte; 0.15≤X / b≤100. When the contents of the polynitrile additive and the doping element meet the above ranges, especially when 1≤X / b≤50, the polynitrile additive and the doping element act synergistically to further improve the structural stability and thermal stability of the positive electrode active material, and enhance the cycling performance and safety performance of the electrochemical device.
[0102] In some embodiments, the number of formula (I-A2) in the compound represented by formula (IA) is 4 to 10.
[0103] In some embodiments, the polynitrile additive may be an ether polynitrile; the polynitrile additive includes at least one of the compounds represented by formula (I-1) to formula (I-16),
[0104]
[0105]
[0106]
[0107] In some embodiments, the polynitrile additive may further include at least one of the compounds represented by formula (I-17) to formula (I-19):
[0108]
[0109] In some embodiments, the polynitrile additive may be a phosphine polynitrile, and the polynitrile additive includes at least one of the compounds represented by formula (II-1) to formula (II-8).
[0110]
[0111]
[0112] In some embodiments, the polynitrile additive may be a phosphine oxide polynitrile, and the polynitrile additive includes at least one of the compounds represented by formula (II-9) to formula (II-21).
[0113]
[0114]
[0115] In some embodiments, the polynitrile additive may further include at least one of the compounds represented by formula (II-22) to formula (II-24):
[0116]
[0117] [Cyclic sulfonate ester additives for electrolytes]
[0118] In some embodiments, the electrolyte further comprises a cyclic sulfonate additive, wherein the cyclic sulfonate additive comprises a compound represented by formula (III):
[0119]
[0120] wherein D and E are each independently selected from a substituted or unsubstituted C1 to C8 alkylene group, and when substituted, the substituent is selected from a fluorine atom;
[0121] Alternatively, D and E are each independently selected from substituted or unsubstituted C1 to C6 alkylene;
[0122] Further optionally, D and E are each independently selected from substituted or unsubstituted C1 to C4 alkylene;
[0123] L is selected from a covalent single bond or -OS(=O)2-.
[0124] In the embodiment of the present application, during the charge and discharge process of the electrochemical device, the cyclic sulfonate additive can react with the positive electrode active material, and the cyclic sulfonate additive can undergo a reduction ring-opening reaction, thereby forming an interface film on the surface of the positive electrode active material, thereby protecting the positive electrode active material.
[0125] As some examples of cyclic sulfonate additives, the cyclic sulfonate additives may be monosultones, and the cyclic sulfonate additives include compounds represented by formula (III-1),
[0126]
[0127] Among them, R 31 and R 32 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group;
[0128] s is a positive integer from 1 to 4, wherein s is 1, 2, 3 or 4.
[0129] Illustratively, the cyclic sulfonate additive includes one or more of 1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 1,2-butane sultone, 1,3-butane sultone, 2,4-butane sultone and 1,3-pentane sultone.
[0130] As other examples of cyclic sulfonate additives, the cyclic sulfonate additives may be disulfones, and the cyclic sulfonate additives include compounds represented by formula (III-2):
[0131]
[0132] Among them, R 33 and R 34 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group;
[0133] R 35 and R 36 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group;
[0134] r is a positive integer from 1 to 4. When r≥2, multiple R 35 can be the same or different from each other, and multiple R 36 wherein r can be 1, 2, 3 or 4.
[0135] Illustratively, the cyclic sulfonate additives include methylene methanedisulfonate and / or ethylene methanedisulfonate. Such cyclic sulfonate additives can also form an interfacial protective film on the negative electrode, thereby protecting the negative electrode surface and further improving the high-temperature storage performance and cycle performance of the electrochemical device.
[0136] As further examples of cyclic sulfonate additives, cyclic sulfonate additives may include compounds represented by formula (III-1) and compounds represented by formula (III-2). Specific examples of the compounds represented by formula (III-1) and compounds represented by formula (III-2) are as described above and are not repeated here.
[0137] For example, cyclic sulfonate additives may include 1,3-propane sultone (PS), 1,4-butane sultone (BS), and methylene methane disulfonate (MMDS). These additives have excellent film-forming effects on the surfaces of positive and negative electrodes and are relatively low in cost.
[0138] In some embodiments, the mass percentage of the cyclic sulfonate additive is c%, based on the weight of the electrolyte, with 0.10≤c≤10. When the cyclic sulfonate additive meets the aforementioned mass percentage, it forms a good film on the surfaces of the positive and negative electrodes, and the density of the interfacial protective film is high, which can further improve the protection of the positive and negative electrode surfaces. On the one hand, the interfacial protective film can reduce the risk of electron transfer between the positive electrode, electrolyte, and negative electrode to a certain extent, thereby reducing the adverse effects of side reactions caused by electron transfer. In addition, the moderate thickness of the interfacial protective film can ensure the effective transmission of lithium ions in the interfacial protective film, facilitate the intercalation and deintercalation of lithium ions during the cycle, and thus reduce the cycle impedance.
[0139] In some embodiments, the ratio of the mass percentage of the doping element b% to the mass percentage of the cyclic sulfonate additive c% satisfies: 0.005≤b / c≤20.
[0140] [Electrolyte salt for electrolyte solution]
[0141] The electrolyte solution of the present application also contains an electrolyte salt. The electrolyte salt is an electrolyte salt known in the art and suitable for use in electrochemical devices. Suitable electrolyte salts can be selected for different electrochemical devices. For example, for lithium-ion batteries, lithium salts are typically used as the electrolyte salt.
[0142] In some embodiments, the lithium salt includes or is selected from at least one of an organic lithium salt and an inorganic lithium salt.
[0143] In some embodiments, the lithium salt includes or is selected from lithium hexafluorophosphate (LiPF6), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium perfluorobutylsulfonate (LiC4F9SO3), lithium perchlorate (LiClO4), lithium aluminate (LiAlO2), lithium tetrachloroaluminate (LiAlCl4), lithium bis(fluorosulfonyl)imide (LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2), where x and y are natural numbers), at least one of lithium chloride (LiCl) or lithium fluoride (LiF). In some embodiments, the weight percentage of the lithium salt in the electrolyte of the present application is 10 wt% to 15 wt%, for example, 10%, 11%, 12%, 13%, 14%, 15%, or any range therebetween.
[0144] [Non-aqueous organic solvent for electrolyte]
[0145] The electrolyte of the present application further comprises a non-aqueous organic solvent. In some embodiments, the non-aqueous organic solvent comprises at least one of a carbonate, a carboxylate, an ether compound, a sulfone compound, or other aprotic solvent. In some embodiments, the weight percentage of the non-aqueous organic solvent is 21% to 90%, for example, 21%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or any range therebetween.
[0146] In some embodiments, the carbonate solvent comprises at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, dipropyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, and bis(2,2,2-trifluoroethyl)carbonate.
[0147] In some embodiments, the carboxylate solvent comprises at least one of methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, γ-butyrolactone, valerolactone, and butyrolactone.
[0148] In some embodiments, the ether compound solvent comprises at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, bis(2,2,2-trifluoroethyl) ether, 1,3-dioxane, and 1,4-dioxane.
[0149] In some embodiments, the sulfone compound comprises at least one of ethyl vinyl sulfone, methyl isopropyl sulfone, isopropyl sec-butyl sulfone, and sulfolane.
[0150] The non-aqueous organic solvent in the electrolyte may be a single non-aqueous organic solvent or a mixture of multiple non-aqueous organic solvents. When a mixed solvent is used, the mixing ratio can be controlled according to the desired performance of the electrochemical device.
[0151] [positive electrode]
[0152] The positive electrode is a positive electrode known in the art and can be used in an electrochemical device. In some embodiments, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer is disposed on the surface of the positive electrode current collector. The positive electrode active material layer comprises a positive electrode active material.
[0153] In some embodiments, the structure of the positive electrode is a structure of a positive electrode known in the art that can be used in electrochemical devices.
[0154] In some embodiments, the positive electrode current collector is a metal, such as but not limited to aluminum foil.
[0155] The positive electrode active material can be selected from various conventionally known substances that are known in the art and can be used as positive electrode active materials for electrochemical devices and can reversibly intercalate and deintercalate active ions.
[0156] In some embodiments, the positive electrode active material comprises lithium and a composite oxide of at least one selected from cobalt, manganese and nickel. Specifically, the following compounds may be used: LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(Ni a Co b Mn c )O2(0 <a<1,0<b<1,0<c<1,a+b+c=1)、LiMn2O4LiNi 1-y Co y O2、LiCo l-y Mn y O2、LiNi l-y Mn y O2(0 <y<1)、Li(Ni a Mn b Co c )04(0 <a<2,0<b<2,0<c<2,a+b+c=2)、LiMn 2-z Ni z O4、LiMn 2-z Co z O4(0 <z<2)、Li(Ni a Co b Al c)At least one or a mixture of two or more of O2(0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiCoPO4, and LiFePO4. In some embodiments, the positive electrode active material further includes at least one of sulfides, selenides, and halides.
[0157] Exemplarily, the main material of the positive electrode active material can be lithium cobalt oxide LiCoO2. During the charging process, lithium ions will continuously escape and embed into the negative electrode. As the lithium ions escape, the crystal phase structure of lithium cobalt oxide may change, which may lead to a tendency for the structure to be damaged. Although the doping mechanism is not clear, there are doping elements (such as one or more of aluminum Al, magnesium Mg, zirconium Zr, titanium Ti, and lanthanum La elements) doped in lithium cobalt oxide. The doping elements may occupy lithium positions, etc., thereby improving the structural stability of lithium cobalt oxide after detachment, and the thermal stability of lithium cobalt oxide is also significantly improved. In some other examples, the main material of the positive electrode active material can also be lithium manganate, lithium nickelate, etc., which can be selected according to requirements.
[0158] In some embodiments, the mass percentage content b% of the doping element satisfies 0.01 ≤ b ≤ 0.5. When the mass percentage content of the doping element satisfies the above range, it can significantly improve the thermal stability of the positive electrode active material and improve the cycling performance of the electrochemical device.
[0159] In some embodiments, the doping element can be magnesium Mg. When magnesium Mg is doped into the positive electrode active material, it can significantly improve the thermal box performance and cycling performance of the electrochemical device. The possible reason is that Mg doping can effectively occupy the transition metal position or lithium position of the positive electrode material, significantly improving the structural stability of the positive electrode material after de-lithiation, and thus significantly improving the cycling performance of the electrochemical device. Mg doping can effectively improve the thermal stability of the positive electrode material, and thus also has a good improvement effect on the thermal box.
[0160] In some embodiments, when the doping element is magnesium Mg, the mass percentage content b1% of Mg satisfies 0.01 ≤ b1 ≤ 0.5. When the mass percentage content of Mg satisfies the above range, it can, on the basis of improving the structural stability of the positive electrode active material, ensure a lower impedance of the electrochemical device and basically does not affect the capacity per gram of the positive electrode active material, thereby ensuring the cycling performance of the electrochemical device.
[0161] In addition, 0.15 ≤ X / b1 ≤ 100 is satisfied between Mg and the polycyano additive; especially when 1 ≤ X / b ≤ 150, Mg and the polycyano additive can work synergistically to improve the thermal box performance and cycling performance of the electrochemical device.
[0162] In some embodiments, the positive electrode active material includes first particles and second particles, wherein the average particle size of the first particles is larger than the average particle size of the second particles. Using first and second particles of various particle sizes in the positive electrode active material can improve the compaction density of the positive electrode, thereby increasing the energy density of the electrochemical device.
[0163] In some embodiments, the positive electrode active material satisfies at least one of the following conditions:
[0164] The Dv50 of the first particle satisfies: 10 μm ≤ Dv50 ≤ 15 μm;
[0165] The Dv99 of the first particle satisfies: 20 μm ≤ Dv99 ≤ 30 μm;
[0166] The ratio between Dv50 and Dv99 of the first particle satisfies: 1.5≤Dv99 / Dv50<3;
[0167] The Dv50' of the second particle satisfies: 2 μm ≤ Dv50' ≤ 6 μm;
[0168] The Dv50 of the first particle and the Dv50' of the second particle satisfy: 2≤Dv50 / Dv50'<8.
[0169] In some embodiments, the ratio between the Dv50 of the first particle and the mass percentage X of the polynitrile additive satisfies: 7≤Dv50 / X≤50; alternatively, 10≤Dv50 / X≤30. Given that the smaller the particles of the positive electrode active material, the larger their specific surface area is, the more area in contact with the electrolyte, and the more likely they are to undergo side reactions with the electrolyte, resulting in poorer structural and thermal stability of the positive electrode active material itself. Therefore, in the embodiments of the present application, the particle size of the first particle and the amount of the polynitrile additive used are coordinated to provide a more effective protective effect for the first particle, thereby improving the structural stability and thermal stability of the positive electrode active material.
[0170] In some embodiments, after the electrochemical device is fully charged to 4.5 V (meaning the electrochemical device is charged to 4.5 V at a constant current of 0.2 C, and then charged to 0.05 C at a constant voltage at 4.5 V), the positive electrode is tested using differential scanning calorimetry (DSC), and an exothermic peak is observed at 250° C. to 300° C., indicating that the thermal stability of the positive electrode active material is relatively high.
[0171] In some embodiments, the positive electrode active material layer further comprises a positive electrode binder and a positive electrode conductor. The positive electrode binder is used to improve the bonding performance between the positive electrode active material particles and between the positive electrode active material particles and the current collector. In some embodiments, the positive electrode binder includes at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, and nylon. The positive electrode conductor is used to provide conductivity to the electrode and may include any conductive material as long as it does not cause chemical changes. In some embodiments, the positive electrode conductor is at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, metal powder, metal fiber, and polyphenylene derivatives. In some embodiments, the metal in the metal powder and metal fiber includes at least one of copper, nickel, aluminum, and silver.
[0172] In some embodiments, the positive electrode preparation method is a method for preparing a positive electrode that can be used in an electrochemical device as is known in the art. In some embodiments, during the preparation of the positive electrode slurry, a solvent is typically added, and the positive electrode active material is added with a binder and, as needed, a conductive material and a thickener, and then dissolved or dispersed in the solvent to form the positive electrode slurry. The solvent evaporates and is removed during the drying process. The solvent is a solvent that is known in the art and can be used as a positive electrode active material layer, such as, but not limited to, N-methylpyrrolidone (NMP).
[0173] [negative electrode]
[0174] The negative electrode is a negative electrode known in the art and can be used in an electrochemical device. In some embodiments, the negative electrode comprises a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is disposed on the surface of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material.
[0175] In some embodiments, the structure of the negative electrode is a structure of a negative electrode known in the art that can be used in electrochemical devices.
[0176] In some embodiments, the negative electrode current collector is a metal, such as but not limited to copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0177] The negative electrode active material can be selected from various conventional substances known in the art that can be used as negative electrode active materials for electrochemical devices and can reversibly embed and de-embeduce active ions, or conventional substances that can reversibly dope and de-dope active ions.
[0178] In some embodiments, the negative electrode active material includes at least one of lithium metal, lithium metal alloy, carbon material, material capable of doping / dedoping lithium, or transition metal oxide. In some embodiments, the carbon material can be selected from various carbon materials well-known in the art that can be used as carbon-based negative electrode active materials for electrochemical devices. In some embodiments, the carbon material includes at least one of crystalline carbon and amorphous carbon. In some embodiments, the crystalline carbon is natural graphite or artificial graphite. In some embodiments, the shape of the crystalline carbon is amorphous, plate-shaped, flake-shaped, spherical or fibrous. In some embodiments, the crystalline carbon is low-crystalline carbon or high-crystalline carbon. In some embodiments, the low-crystalline carbon includes at least one of soft carbon and hard carbon. In some embodiments, the high-crystalline carbon includes at least one of natural graphite, crystalline graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbead, mesophase pitch, and high-temperature calcined carbon.
[0179] In some embodiments, the high-temperature calcined carbon is petroleum coke or coke derived from coal tar pitch. In some embodiments, the amorphous carbon includes at least one of soft carbon, hard carbon, mesophase pitch carbonization product, and calcined coke. In some embodiments, the negative electrode active material includes a transition metal oxide. In some embodiments, the transition metal oxide includes at least one of vanadium oxide and lithium vanadium oxide. In some embodiments, the negative electrode active material includes at least one of Si, SiOx (0 < x < 2), Si / C composite, Si-Q alloy, Sn, SnOz, Sn-C composite, Sn-R alloy, where Q is selected from at least one of alkali metals, alkaline earth metals, Group 13 to Group 16 elements, transition elements, and rare earth elements and Q is not Si, and R is selected from at least one of alkali metals, alkaline earth metals, Group 13 to Group 16 elements, transition elements, and rare earth elements and R is not Sn. In some embodiments, Q and R include at least one of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po.
[0180] In some embodiments, the negative electrode active material layer further comprises a negative electrode binder and a negative electrode conductive agent. In some embodiments, the negative electrode binder comprises at least one of difluoroethylene-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon. In some embodiments, the negative electrode conductive agent is used to provide conductivity to the electrode and may include any conductive material as long as it does not cause chemical changes. In some embodiments, the negative electrode conductive agent comprises any one of a carbon-based material, a metal-based material, and a conductive polymer, or a mixture thereof. In some embodiments, the carbon-based material comprises at least one of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber. In some embodiments, the metal-based material comprises at least one of metal powder or metal fiber of copper, nickel, aluminum, silver, etc. In some embodiments, the conductive polymer comprises a polyphenylene derivative.
[0181] In some embodiments, the method for preparing the negative electrode is a method for preparing a negative electrode that can be used in an electrochemical device that is well known in the art. In some embodiments, in the preparation of the negative electrode slurry, a solvent is generally added, and the negative electrode active material is added with a binder and, if necessary, a conductive material and a thickener, and then dissolved or dispersed in the solvent to form the negative electrode slurry. The solvent is evaporated and removed during the drying process. The solvent is a solvent that is well known in the art and can be used as a negative electrode active material layer, and the solvent is, for example, but not limited to, water. The thickener is a thickener that is well known in the art and can be used as a negative electrode active material layer, and the thickener is, for example, but not limited to, sodium carboxymethyl cellulose.
[0182] The present application has no particular limitation on the mixing ratio of the negative electrode active material, the binder, and the thickener in the negative electrode active material layer, and the mixing ratio can be controlled according to the desired performance of the electrochemical device.
[0183] [Isolation film]
[0184] The separator is any separator known in the art and can be used in electrochemical devices, such as, but not limited to, a polyolefin microporous membrane. In some embodiments, the separator comprises at least one of polyethylene (PE), ethylene-propylene copolymer, polypropylene (PP), ethylene-butene copolymer, ethylene-hexene copolymer, and ethylene-methyl methacrylate copolymer.
[0185] In some embodiments, the isolation film is a single-layer isolation film or a multi-layer isolation film.
[0186] In some embodiments, the isolation film is coated with a coating. In some embodiments, the coating comprises at least one of an organic coating and an inorganic coating, wherein the organic coating is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyimide, acrylonitrile-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, acrylic acid-styrene copolymer, polydimethylsiloxane, sodium polyacrylate, and sodium carboxymethyl cellulose, and the inorganic coating is selected from at least one of SiO2, Al2O3, CaO, TiO2, ZnO2, MgO, ZrO2, and SnO2.
[0187] The present application has no particular limitation on the shape and thickness of the separator. The preparation method of the separator is a method well known in the art and can be used for separators of electrochemical devices.
[0188] Based on the same inventive concept, the present application also provides an electronic device.
[0189] The electronic device of the present application is any electronic device, such as but not limited to a laptop computer, a pen-type computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor. It should be noted that the electrochemical device of the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic devices listed above. Air vehicles include both air vehicles within the atmosphere and air vehicles outside the atmosphere.
[0190] In some embodiments, the electronic device comprises the electrochemical device described above.
[0191] The following uses lithium-ion batteries as an example and combines comparative examples and examples to further illustrate the technical solution of the present application, but is not limited thereto. Those skilled in the art will understand that the preparation method described in this application is only an exemplary embodiment, and any modification or replacement of the technical solution of this application that does not depart from the scope of the technical solution of this application should be included in the scope of protection of this application.
[0192] In the following examples and comparative examples, all reagents, materials and instruments used can be commercially available or synthesized unless otherwise specified.
[0193] Examples and Comparative Examples
[0194] Preparation of lithium-ion batteries
[0195] (1) Preparation of positive electrode
[0196] The positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; the aluminum foil is dried, then cold pressed, cut into pieces, slit, and dried under vacuum conditions to obtain the positive electrode.
[0197] The conventional positive electrode active material is selected from lithium cobalt oxide (LiCoO2).
[0198] Preparation of modified positive electrode active materials:
[0199] Lithium cobalt oxide (LiCoO2), a positive electrode active material, and an oxide containing a metal element M (at least one of magnesium oxide (MgO), titanium dioxide (TiO2), and aluminum oxide (Al2O3)) were mixed in a mixer at 300 rpm for 20 minutes. After mixing, the mixture was placed in an air kiln and heated to 820°C at 5°C / min, held for 24 hours, cooled naturally, and then removed and passed through a 300-mesh sieve to obtain a modified positive electrode active material (i.e., modified LiCoO2). The total content of the metal elements M (Mg, Ti, and Al) in this modified positive electrode active material was 7000 ppm, with a molar ratio of Mg, Ti, and Al of 1:1:1. The specific types of the M elements are shown in Tables 1 to 4.
[0200] (2) Preparation of negative electrode
[0201] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene-butadiene rubber (SBR) and the thickener sodium carboxymethyl cellulose (CMC) were mixed in a weight ratio of 95:2:2:1, deionized water was added, and a negative electrode slurry was obtained under the action of a vacuum mixer; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil; the copper foil was dried, then cold pressed, cut into pieces, slit, and dried under vacuum conditions to obtain the negative electrode.
[0202] (3) Preparation of electrolyte
[0203] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:1. Additives were then added, dissolved, and thoroughly stirred before adding lithium salt LiPF6. The mixture was mixed to obtain an electrolyte. The mass content of LiPF6 was 12.5% based on the mass of the electrolyte. The specific types and contents of the additives used in the electrolyte are shown in Tables 1 to 4. The wt% values are all calculated based on the total mass n of the electrolyte.
[0204] (4) Preparation of isolation membrane
[0205] Polyethylene PE porous polymer film is used as the isolation membrane.
[0206] (5) Preparation of lithium-ion batteries
[0207] The positive electrode, separator, and negative electrode are stacked in order, so that the separator is placed between the positive electrode and the negative electrode to play an isolating role. Then the tabs are welded and wound to obtain an electrode assembly. The electrode assembly is placed in an outer packaging foil aluminum-plastic film and injected with the prepared electrolyte. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, a soft-pack lithium-ion battery is obtained.
[0208] Performance testing:
[0209] 1. Storage expansion rate of lithium-ion batteries at 80°C
[0210] The lithium-ion battery was discharged at 0.5C to 3.0V at 25°C, then charged at 0.5C to 4.5V, and then charged at a constant voltage of 0.05C at 4.5V. The thickness of the lithium-ion battery was measured with a PPG soft pack battery thickness gauge (500g pressure) and recorded as H. 11 , placed in an 80℃ oven, constant voltage of 4.5V for 7 hours, after 7 hours, use PPG soft pack battery thickness gauge to test (500g pressure) and record the thickness of the battery, recorded as H 12 .
[0211] Thickness expansion rate = (H 12 -H 11 ) / H 11 *100%.
[0212] 2. High temperature cycle test of lithium-ion batteries at 45°C
[0213] Place the lithium-ion battery in a 45°C thermostat and let it rest for 30 minutes to allow the lithium-ion battery to reach a constant temperature. The lithium-ion battery that has reached a constant temperature is then charged at 45°C at a constant current of 0.2C to 4.5V, then charged at a constant voltage of 0.05C at 4.5V, left to rest for 5 minutes, and then discharged at a constant current of 0.2C to 3.0V. The battery is then left to rest for 5 minutes, and the initial capacity is tested. The battery is then charged at a constant current of 1.3C to 4.15V, then charged at a constant voltage of 1C at 4.15V, and then charged at a constant current of 1C to 4.25V. The battery is then charged at a constant current of 1C to 4.25V, and then charged at a constant voltage of 0.8 at 4.25V. The battery is then charged at a constant current of 0.8C to 4.5V, and then charged at a constant voltage of 0.05C at 4.5V, left to rest for 5 minutes, and then discharged at a constant current of 1C to 3.0V, left to rest for 5 minutes. This constitutes one charge and discharge cycle. Calculate the capacity retention of the lithium-ion battery after 400 cycles of charge / discharge.
[0214] Capacity retention rate (%) of a lithium-ion battery after N cycles = discharge capacity at the Nth cycle / discharge capacity at the first cycle × 100%.
[0215] Measure the thickness of the lithium-ion battery and calculate the thickness expansion rate of the lithium-ion battery according to the following formula:
[0216] Thickness expansion ratio = (battery thickness after cycling - battery thickness before cycling) / battery thickness before cycling * 100%.
[0217] 3. Intermittent high temperature cycle test of lithium-ion batteries at 45°C
[0218] In a 45°C constant temperature box, the lithium-ion battery was charged at a constant current of 1C to 4.5V, and then at a constant voltage of 4.5V to a current of 0.05C; placed at 45°C for 19.5 hours, then discharged at a constant current of 0.5C to 3V and allowed to stand for 10 minutes; this was counted as one cycle, and the process was repeated, recording the thickness change and capacity retention rate of the lithium-ion battery until severe flatulence occurred or the cycle capacity retention rate dropped to 60% and the test was stopped;
[0219] Capacity retention rate of lithium-ion battery after M cycles (%) = discharge capacity of the Mth cycle / discharge capacity of the first cycle × 100%
[0220] 4. Lithium-ion battery hot-box test
[0221] At 25°C, charge the lithium-ion battery at a constant current of 0.7C to 4.5V, and then at a constant voltage of 4.5V to a current of 0.05C. Place the battery in a hot box and heat it to 135°C at a temperature ramp rate of 5±2°C / minute. Hold for 1 hour, and record the changes in the battery voltage, temperature, and hot box temperature. The battery passes the test if it does not catch fire, explode, or emit smoke. Ten batteries are tested per group, and the number of batteries that pass the test is recorded.
[0222] 5. Lithium-ion battery DC resistance DCR (25°C) test
[0223] Place the lithium-ion battery in a 25°C constant temperature box for 1 hour to allow the lithium-ion battery to reach a constant temperature; charge it to 4.2V at a constant current of 0.5C, then charge it to 4.5V at a constant current of 0.3C, charge it to a current of 0.02C at 4.5V, and let it stand for 30 minutes; then discharge it to 3.4V at a constant current of 0.1C, let it stand for 30 minutes, and use the capacity of this step as the benchmark. At 0°C, charge it to 4.2V at a constant current of 0.5C, then charge it to 4.5V at a constant current of 0.3C, and charge it to a current of 0.02C at 4.5V, and let it stand for 30 minutes; discharge it at a constant current of 0.1C for 60min (calculated using the actual capacity obtained in the previous step), and record the voltage at this time as V1; then discharge it at a constant current of 1C for 1s (the capacity is calculated based on the battery's labeled capacity), and record the voltage at this time as V2, and calculate the DC impedance corresponding to the battery's 20% SOC state.
[0224] 20% SOC DC resistance = (V1-V2) / 1C.
[0225] Performance test results:
[0226] Table 1 Electrolytes and test results of Examples 1 to 45 and Comparative Example 1
[0227]
[0228]
[0229] As shown in Table 1, in Comparative Example 1, no doping element was added to the positive electrode active material, and no polynitrile additive was added to the electrolyte. The cycle performance and hot box performance of the battery were relatively poor.
[0230] Compared with Comparative Example 1, Comparative Examples 2 to 5 all added doping elements to the positive electrode active material or added polynitrile additives to the electrolyte. Although the cycle performance and / or hot-box performance of the battery were improved, they could not meet the requirements.
[0231] Compared to the comparative example, the embodiment doped the positive electrode active material with elements such as Mg / Al / Ti. These elements effectively occupy the transition metal or lithium sites of the positive electrode active material during the sintering process, which can improve the structural stability and thermal stability of the positive electrode active material after delithiation, thereby ensuring the structural stability of the positive electrode active material. The polynitrile additive can effectively complex with the transition metal on the surface of the positive electrode active material to form a stable interface protective film at the interface of the positive electrode active material. On the one hand, it can effectively inhibit the dissolution of transition metals on the surface of the positive electrode active material; on the other hand, it can effectively isolate the contact between the interface of the positive electrode active material and the electrolyte, reducing side reactions at the interface of the positive electrode active material.
[0232] The doping elements and polynitrile additives work synergistically to stabilize the internal and surface structures of the cathode active material after delithiation, thereby effectively improving the battery's cycling performance at high temperatures. Polynitrile additives can effectively inhibit side reactions at the cathode active material interface, reducing interfacial heat generation. Doping the cathode active material can improve its thermal stability. The doping elements and polynitrile additives not only reduce interfacial heat generation but also enhance the thermal stability of the cathode active material itself, effectively enhancing battery safety.
[0233] Table 2 Test results of Comparative Example 2 and Examples 46 to 53
[0234]
[0235] As can be seen from Table 2, the electrolytes of Examples 46 to 53 have the same composition as that of the electrolyte of Comparative Example 2, but the doping element Mg is added to the positive electrode active materials in Examples 46 to 53; Mg element doping can effectively occupy the transition metal site or lithium site of the positive electrode active material, and significantly improve the structural stability of the positive electrode active material after delithiation, thereby significantly improving the cycle performance of the battery. Mg element doping can effectively improve the thermal stability of the positive electrode active material, so it also has a good improvement effect on the hot box. When the Mg element doping amount is high, the overall impedance of the battery increases significantly, and it will affect the gram capacity of the positive electrode active material, thereby affecting the overall cycle performance of the battery. When the Mg doping amount and the ratio of the polynitrile additive are within a limited range, the hot box performance and cycle performance of the battery can be significantly improved.
[0236] Table 3 Test results of Comparative Example 2 and Examples 54 to 74
[0237]
[0238]
[0239] As shown in Table 3, Examples 54 to 74 improve the particle size based on Example 4. When the positive electrode active material satisfies the following conditions: Dv50 of the first particle is within the range of 10 μm to 15 μm; Dv99 of the first particle is within the range of 20 μm to 30 μm; Dv50' of the second particle is within the range of 2 μm to 6 μm; 1.5 ≤ Dv99 / Dv50 < 3; and / or 2 ≤ Dv50 / Dv50' < 8, the high-temperature storage expansion rate and cycle capacity retention rate of the lithium-ion battery under high-voltage operating conditions can be further improved.
[0240] When the second particles of the positive electrode active material contain secondary particles and the average particle size of the primary particles forming the secondary particles is 0.1 μm to 3 μm, it helps to further improve the high-temperature storage expansion rate and cycle capacity retention rate of the lithium-ion battery under high voltage working conditions.
[0241] Table 4 Electrolytes and test results of Comparative Example 2 and Examples 75 to 85
[0242]
[0243]
[0244] As can be seen from Table 4, Examples 75 to 85 are further improvements based on Example 4. In Examples 75 to 85, cyclic sulfonate additives are further added to the electrolyte. Cyclic sulfonate additives can further improve the high-temperature cycle performance of lithium-ion batteries and reduce the DC impedance of lithium-ion batteries. The reason may be that the cyclic sulfate compound can form an interface film with excellent mechanical stability on the surface of both the positive and negative electrodes. The interface film can significantly inhibit the side reactions at the positive and negative electrode interfaces, further improve the thermal stability and mechanical stability of the interface film, and improve the cycle performance and high-temperature storage performance.
[0245] Furthermore, when the mass percentage c% of the cyclic sulfonate additive is too low, for example, less than 0.01%, the cyclic sulfonate additive may not form a complete and effective organic film on the positive and negative electrode surfaces, resulting in a weaker protective capability for the positive and negative electrode surfaces. However, when the mass percentage c% of the cyclic sulfonate additive is too high, the film formed is thicker, potentially hindering the migration of lithium ions. Therefore, in the embodiment, when 0.10% ≤ c ≤ 10%, the formed interfacial film can effectively protect the positive and negative electrodes and ensure smooth lithium ion migration. Furthermore, the synergistic combination of the cyclic sulfonate additive and the polynitrile additive can further improve the cycling performance and high-temperature storage performance of lithium-ion batteries.
[0246] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions, and modifications may be made to the embodiments without departing from the spirit, principles, and scope of the present application.
Claims
1. An electrochemical device comprising: negative electrode; A positive electrode comprising a positive electrode active material containing a doping element, wherein the doping element comprises one or more of aluminum (Al), magnesium (Mg), zirconium (Zr), titanium (Ti), and lanthanum (La), wherein the mass percentage of the doping element is b% based on the mass of the positive electrode active material, and 0.01≤b≤3; a separator, disposed between the negative electrode and the positive electrode; as well as An electrolyte comprising a polynitrile additive, wherein the polynitrile additive comprises a compound represented by formula (IA) and / or a compound represented by formula (II-A), In Formula IA, A 11 、A 12 、A 13 Each independently selected from formula (I-A1), formula (I-A2), In Formula IA, n is a positive integer from 1 to 8, wherein when there are multiple A 11 When multiple A 11 Can be the same or different, the A 11 、A 12 、A 13 At least two of which are selected from I-A2; In formula II-A, Q is selected from one of formula (II-A1) and formula (II-A2); In formula II-A, m is selected from 1 or 2; R 11 、R 12 、R 13 、R 21 、R 22 、R 23 are independently selected from a covalent single bond, a substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkynyl, substituted or unsubstituted C6-C 10 aryl, substituted or unsubstituted C3-C 10 alicyclic hydrocarbon group, substituted or unsubstituted C1-C 10 The heterocyclic group, substituted or unsubstituted heteroatom-containing functional group, when R 11 、R 12 、R 13 、R 21 、R 22 、R 23 When at least one of is substituted, the substituent is selected from halogen; The heterocyclic group includes at least one of an aliphatic heterocyclic group and an aromatic heterocyclic group; in, Indicates the binding site with the adjacent atoms.
2. The electrochemical device according to claim 1, wherein Based on the mass of the electrolyte, the mass percentage of the polynitrile additive is X%; 0.15≤X / b≤100; optionally, 1≤X / b≤50.
3. The electrochemical device according to claim 1, wherein The number of formula (I-A2) in the compound represented by formula (IA) is 4 to 10.
4. The electrochemical device according to any one of claims 1 to 3, wherein The polynitrile additive includes at least one of the compounds represented by formula (I-1) to formula (I-19), 5. The electrochemical device according to any one of claims 1 to 4, wherein The polynitrile additive includes at least one of the compounds represented by formula (II-1) to formula (II-21), 6. The electrochemical device according to any one of claims 1 to 5, wherein The electrolyte further includes a cyclic sulfonate additive, wherein the cyclic sulfonate additive includes a compound represented by formula (III), wherein D and E are each independently selected from a substituted or unsubstituted C1 to C8 alkylene group, and when substituted, the substituent is selected from a fluorine atom; Alternatively, D and E are each independently selected from substituted or unsubstituted C1 to C6 alkylene; Further optionally, D and E are each independently selected from substituted or unsubstituted C1 to C4 alkylene; L is selected from a covalent single bond or -OS(=O)2-.
7. The electrochemical device according to claim 6, wherein The cyclic sulfonate additive includes a compound represented by formula (III-1), Among them, R 31 and R 32 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group; s is a positive integer from 1 to 4.
8. The electrochemical device according to claim 6 or 7, wherein The cyclic sulfonate additive includes a compound represented by formula (III-2), Among them, R 33 and R 34 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group; R 35 and R 36 Each is independently selected from a hydrogen atom, a halogen atom, and a C1 to C4 alkyl group; r is a positive integer from 1 to 4. When r≥2, multiple R 35 can be the same or different from each other, and multiple R 36 They may be the same as or different from each other.
9. The electrochemical device according to any one of claims 6 to 8, wherein The cyclic sulfonate additive includes one or more of 1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 1,2-butane sultone, 1,3-butane sultone, 2,4-butane sultone, 1,3-pentane sultone, methylene methanedisulfonate or ethylene methanedisulfonate.
10. The electrochemical device according to any one of claims 6 to 9, wherein Based on the weight of the electrolyte, the mass percentage of the cyclic sulfonate additive is c%, 0.10≤c≤10; Optionally, the ratio of the mass percentage b% of the doping element to the mass percentage c% of the cyclic sulfonate additive satisfies: 0.005≤b / c≤20.
11. The electrochemical device according to any one of claims 1 to 10, wherein The doping element is magnesium Mg; Optionally, 0.01≤b≤0.
5.
12. The electrochemical device according to any one of claims 1 to 11, wherein The positive electrode active material includes first particles and second particles, wherein the average particle size of the first particles is larger than the average particle size of the second particles; Optionally, the positive electrode active material satisfies at least one of the following conditions: The Dv50 of the first particles satisfies: 10 μm ≤ Dv50 ≤ 15 μm; The Dv99 of the first particles satisfies: 20 μm ≤ Dv99 ≤ 30 μm; The ratio between Dv50 and Dv99 of the first particles satisfies: 1.5≤Dv99 / Dv50<3; The Dv50′ of the second particles satisfies: 2 μm ≤ Dv50′ ≤ 6 μm; The Dv50 of the first particle and the Dv50′ of the second particle satisfy: 2≤Dv50 / Dv50′<8.
13. The electrochemical device according to claim 12, wherein The ratio between Dv50 of the first particles and the mass percentage content X of the polynitrile additive satisfies: 7≤Dv50 / X≤50; optionally, 10≤Dv50 / X≤30.
14. The electrochemical device according to any one of claims 1 to 13, wherein After the electrochemical device was fully charged to 4.5 V, the positive electrode was tested using differential scanning calorimetry, which showed an exothermic peak at 250° C. to 300° C.
15. An electronic device comprising the electrochemical device according to any one of claims 1 to 14.
Citation Information
Patent Citations
Positive electrode active material, and electrochemical device and electronic device using same
CN113078309A
Electrochemical device and electronic device comprising same
CN114365319A
Electrolyte solution, electrochemical device, and electronic device
CN114400375A
Cited By
Secondary battery and electronic device
CN121366931A
Secondary battery and electronic device
CN121394514A